Designing an illustrated book as an educational medium to introduce Ronggeng Gunung dance to the younger generation: an effort to preserve traditional dance - Jazuli Abdin Moenib; Saiddah Nisa Sondara (Institut Seni Indonesia Surakarta, 2023)
This research delves into Ronggeng Gunung dance, a traditional folk art from West Java, Indonesia, which, despite its cultural significance, remains relatively unknown. The study focuses on the crucial task of introducing this dance form to the younger generation, leveraging their receptiveness and curiosity. The primary objective is achieved through an illustrated book, offering a visual journey into the cultural roots and historical context of Ronggeng Gunung. The research extends beyond documentation by integrating educational aspects, providing insights into dance attire and musical components, and a comparative analysis of the dance's evolution over time. To accomplish this, a qualitative descriptive method is employed, grounded in accurate facts. Diverse data collection methods include a Literature Study covering books, articles, and journals related to Ronggeng Gunung dance, Observation of the traditional art form through archival and documentary examination, and Interviews with original sources to obtain authentic information. Additionally, Questionnaires assess the younger generation's interest in traditional dance, their knowledge of Ronggeng Gunung, and their preferences for the illustrated book's style. The overarching aim is to cultivate awareness and facilitate the preservation of traditional Ronggeng Gunung dance. After meticulous data collection and analysis, the research advances through design, media, and visual concepts, culminating in the creation of the illustrated book. A beta test validates its impact on the younger generation, demonstrating that the incorporation of a popular illustration style effectively captivates the audience. This outcome underscores the success of the book in fostering a more engaging and comprehensible understanding of the Ronggeng Gunung dance narrative for the younger audience.